Applications of calixarenes in cancer chemotherapy: facts and perspectives - Ali, Yousaf; Abd Hamid, Shafida; M Bunnori, Noraslinda; AA, Ishola (Dove Press, 2015)
Research on therapeutic applications of calixarene derivatives is an emerging area of interest. The anticancer activity of various functionalized calixarenes has been reported by several research group. Due to their superior geometric shape, calixarenes can accommodate drug molecules by forming inclusion complexes. Controlled release of anticancer potential of the calixarenes and their drug loading properties. The potential use of calixarenes in chemoradiotheraphy is also highlighted in brief.